Crafting, connecting, and commoning in everyday maker projects. Issue 156 (December 2021) - Einarsson, Árni Már
Highlights: Thirteen makers projects are analyzed from an everyday life perspective and three types of practices are derived. The practices are crafting that is an individual, recreative, skillful, and immersive practice that connects to an individual workspace aside from the makerspace, connecting that is a creative, object-oriented, and interventionist practice that connects to everyday life situations open for inventions, and commoning that is a social and communal practice that connects to the makerspace community. The practices are discussed in relation to the agency of the maker and spatial practices in makerspace, including barriers of inclusion. Abstract: Makerspaces have spread to schools, museums, and libraries around the world. These are spaces that make technology construction more accessible and afford practices that situate makers as everyday designers. In this paper, the connection between makerspaces and makers' everyday lives is examined. For this study, thirteen makers were interviewed about the process of their everyday maker projects, and the data material was analyzed for practices, reflections on agency, and relations to places like the makerspace, the home, and beyond. Three distinct practices have been discovered and are described. Crafting is an individual, recreative, skillful, and immersive practice that connects to an individual workspace aside from the makerspace. Connecting is a creative, object-oriented, and interventionist practice that connects to everyday life situations open for inventions. Commoning is a social and communal practice that connects to the makerspace community. The makers' practices inform a discussion of the agency the makerspace enables, and the spatial practices that both enable and constrain actions. Also, because makerspaces are places that intend to make technology construction accessible and inclusive, diversity in maker communities, barriers to inclusion, and strategies to overcome these are discussed.